2003
DOI: 10.1103/physrevb.68.045313
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of confined polaronic excitons in spherical ionic quantum dots

Abstract: We report the results of a variational calculation of the energy and the oscillator strength of the exciton ground state in a spherical ionic quantum dot as a function of radius, assuming infinite potential barriers. The strong interaction of the exciton with optical phonons is taken into account by using an effective potential between the electron and the hole as derived by Pollmann and Büttner. The values of the exciton ground-state energies calculated using this effective potential are compared with the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(45 citation statements)
references
References 47 publications
4
41
0
Order By: Relevance
“…Figure 7 shows the EDS spectra taken from the two regions ͑the polycrystalline film on the sample surface and a group of nanoparticles inside the ma-trix͒ of the annealed ZnO-SiO 2 sample. This was expected considering that the bulk ZnO excitonic Bohr radius is about 2.3 nm, 30 i.e., much smaller than the average ZnO nanocluster size found by GIXRD and TEM in the present work. Figure 8 compares the optical absorption spectra ͑solid line͒ and the RT photoluminescence ͑solid+ symbol line͒ of the fully oxidized ZnO-SiO 2 samples implanted with a fluence of 1.0ϫ 10 17 ions/ cm 2 ͓Fig.…”
Section: -2supporting
confidence: 48%
“…Figure 7 shows the EDS spectra taken from the two regions ͑the polycrystalline film on the sample surface and a group of nanoparticles inside the ma-trix͒ of the annealed ZnO-SiO 2 sample. This was expected considering that the bulk ZnO excitonic Bohr radius is about 2.3 nm, 30 i.e., much smaller than the average ZnO nanocluster size found by GIXRD and TEM in the present work. Figure 8 compares the optical absorption spectra ͑solid line͒ and the RT photoluminescence ͑solid+ symbol line͒ of the fully oxidized ZnO-SiO 2 samples implanted with a fluence of 1.0ϫ 10 17 ions/ cm 2 ͓Fig.…”
Section: -2supporting
confidence: 48%
“…According to the quantum confinement effect, the bandgap of ZnO NWs becomes larger than that of the bulk counterpart [33]. However, no quantum confinement effects were discovered in this study because the ZnO NWs have radii larger than 50 nm, whereas the bulk ZnO exciton Bohr radius is ~2.34 nm [34].…”
Section: Figure 3 Sem Images Of Sensors Fabricated At Different Growmentioning
confidence: 71%
“…though clearly mentioned by Lopez-Ponceet et al[64] that BER increases for Cd doped ZnO alloy with increasing Cd concentration, indicating the relatively larger BER in CdO than ZnO[65]. Similarly, in case of NiO, however, quantitative information available regarding BER is scarce but quantitatively it is reported that BER of NiO is 0.13 nm which is even further lower than ZnO[66,67].…”
mentioning
confidence: 95%